The Atlas Maneuver - Berry, Steve, 1955- (A Cotton Malone novel, 2024)
"1945. In the waning months of World War II, Japan hid vast quantities of gold and other stolen valuables in boobytrapped underground caches all across the Philippines. By 1947 some of that loot was recovered, not by treasure hunters, but by the United States government, which told no one about the find. Instead, those assets were stamped classified, shipped to Europe, and secretly assimilated into something called the Black Eagle Trust. Present day. Retired Justice Department operative, Cotton Malone, is in Switzerland doing a favor for a friend. But what was supposed to be a simple operation turns violent and Cotton is thrust into a war between the world's oldest bank and the CIA, a battle that directly involves the Black Eagle Trust. He quickly discovers that everything hinges on a woman from his past, who suddenly reappears harboring a host of explosive secrets centering around bitcoin. The cryptocurrency is being quietly weaponized, readied for an assault on the world's financial systems, a calculated move that will have devastating consequences. Cotton has no choice. He has to act. But at what cost? From the stolid banking halls of Luxembourg, to the secret vaults of Switzerland, and finally up into the treacherous mountains of southern Morocco, Cotton Malone is stymied at every turn. Each move he makes seems wrong, and nothing works, until he finally comes face-to-face with the Atlas Maneuver"--